Pelatihan PELATIHAN PEMBUKUAN SEDERHANA PADA UMKM DAPUR KITA DI DESA PADANGSAMBIAN DENPASAR - Ni Ketut, Utami Nilawati; Utami Nilawati, Ni Ketut; Dharsika, I Gde Eka (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The growth of micro, small and medium enterprises is currently increasing and has a very large role in creating jobs. Access to capital is one of the main problems faced by micro, small and medium enterprises today. This is because there are still many micro, small and medium business actors who do not make bookkeeping as one of the requirements in helping to find capital in legal financial services. The micro, small and medium enterprise Dapur Kita located in Padangsambian Village, Denpasar is a household business engaged in making food with its main product being grilled rice. In measuring the performance of the business they own, this business actor has not made good and neat bookkeeping, even still mixed with household finances. This is because business actors feel the lack of time in making bookkeeping, do not know how to record simply and there are no qualified human resources to help make records. Through this community service activity, the micro, small and medium enterprise Dapur Kita is given simple bookkeeping training. This training is carried out offline. So that it is hoped that the results of this community service activity, micro, small and medium enterprises are truly able to make simple bookkeeping to support business activities.